The Parkin co-regulated gene product, PACRG, is an evolutionarily conserved axonemal protein that functions in outer-doublet microtubule morphogenesis. - Dawe, H; Farr, H; Portman, N; Shaw, M; Gull, K (2005)
Eukaryotic cilia and flagella are highly conserved structures composed of a canonical 9+2 microtubule axoneme. Comparative genomics of flagellated and non-flagellated eukaryotes provides one way to identify new putative flagellar proteins. We identified the Parkin co-regulated gene, or PACRG, from such a screen. Male mice deficient in PACRG are sterile, but its function has been little explored. The flagellated protozoan parasite Trypanosoma brucei possesses two homologues of PACRG. We performed RNA interference knockdown experiments of the two genes independently and both together. Simultaneous ablation of both proteins produced slow growth and paralysis of the flagellum with consequent effects on organelle segregation. Moreover, using transmission electron microscopy, structural defects were seen in the axoneme, with microtubule doublets missing from the canonical 9+2 formation. The occurrence of missing doublets increased toward the distal end of the flagellum and sequential loss of doublets was observed along individual axonemes. GFP fusion proteins of both PACRG homologues localised along the full length of the axoneme. Our results provide the first evidence for PACRG function within the axoneme, where we suggest that PACRG acts to maintain functional stability of the axonemal outer doublets of both motile and sensory cilia and flagella.